Use of technology in efforts to improve cardiac arrest management: A systematic review - Erna Tri Andini; Ridlwan Kamaluddin (Malahayati International Journal of Nursing and Health Science, 2025)
Background: Cardiac arrest is a critical medical condition that occurs when the heart suddenly stops beating, causing the blood circulation to the entire body, including the brain, to stop. This can lead to brain damage or death. Basic Life Support (BLS) training is an essential element in creating a community that is responsive to medical emergencies. The implementation of BLS has been shown to increase the chance of Return of Spontaneous Circulation (ROSC) in patients experiencing Out-of-Hospital Cardiac Arrest (OHCA) by 40% each year. Purpose: To review and evaluate studies on the use of technology in efforts to improve cardiac arrest management. Method: A systematic literature review study to review and evaluate previous studies on the use of technology to improve cardiac arrest management skills, especially in Basic Life Support (BLS) training. The analysis focused on improving knowledge and skills among health workers and health students. The search for scientific articles was conducted from October-November 2024 using the PICO framework as a guide for article selection. Results: Based on the 6 articles reviewed, the technologies used in BLS training include applications/software, virtual reality (VR), educational games, and video-based learning. Virtual reality with realistic simulations was identified as the most effective medium for improving participants' cognitive and psychomotor skills. Conclusion: Technology plays a significant role in supporting the BLS learning process and improving the quality of medical actions, especially in cardiac arrest management.